Duodenum-Preserving Resection of the Head of the Pancreas: The Significance as a Diagnostic Therapy for the Lesion in the Pancreatic Head - Watanabe, Y. (Hindawi Publishing Corporation, 1996)
A 75-year-old man who was diagnosed as having mucin-producing pancreatic cystic lesion ofthe main pancreatic duct by duodenoscopic examination was reported. Because of the low malignant potential of such lesions, duodenum-preserving resection of the head of the pancreas was performed, and the intra-operative histological examination showed no malig-nancy of the resected pancreatic head and no other surgical procedures, such as lymph-adenectomy nor pancreato-duodenectomy were necessary. The significance of this case report lies in that a less invasive operation should be selected at first to diagnose whether the lesion is malignant or not, and als0 that the selected operation itself must be sufficient to resect an adequate part of the pancreatic tissue involving the cystic lesion, ifnot malignant. Here, we report the process to select the procedure and the surgical technique.